APLIKASI MOBILE PENGAJUAN KREDIT OLEH NASABAH PADA BANK BNI 46 KANTOR KAS PLAJU PALEMBANG - Putra, Ade ; Hutrianto, Hutrianto (Universitas Bina Darma, 2017)
This study was conducted to assist Parties PT Bank BNI 46 Cash Office Plaju Palembang in improving service to customers who wish to apply for credit, by providing a Mobile Credit Application By Customer At PT Bank BNI 46 Cash Office Plaju Palembang, so that the customers who apply for credit can determine the filing status of credit that has been submitted. The development method used Prototype method this is because the prototype method is suitable for making an application system know that yet, which will be no adjustment to match the input both from the PT Bank BNI 46 Cash Office Plaju Palembang as well as from the customer. Stages of the prototype method is used, among others Communication, Quick Plan, Modeling Quick Design, Construction of Prototype and Deployment delevery & Feedback. Keywords: Mobile Application, Prototype, Credits, BNI 46